Field notes contributed by James J. Dinsmore, fall 1988 - Dinsmore, James J.et al (1988)
List of birds and locations contributed by James J. Dinsmore with observers Mark Proescholdt and Beth Proescholdt. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed